Critical Review of Credit Bank System in South Korea: A New Mediator for Lifelong Learning? - Junghwan Kim; Hyewon Park; In Tak Kwon; Pyeong Su Yu (Adult Education Research Conference, 2014)
This study critically analyzes Credit Bank System (CBS) as an emerging open higher education system in South Korea by using critical theory. Specifically, it examines the meaning of CBS degree in Korean credentialism circumstances and reflects CBS meeting needs rationale assumption. Based on the findings, conclusions and implications are discussed.